PERFIL DA AÇÃO DO CETOPROFENO E DO GUARANÁ (Paullinia cupana) E SUA ASSOCIAÇÃO SOBRE MARCADORES DO METABOLISMO: UM ENFOQUE HEPÁTICO, RENAL, HEMATOLÓGICO E OXIDATIVO - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2016)
Inflammation is involved in many diseases affecting much of the world's population. Ketoprofen is a widely used drug in the treatment of these inflammatory processes. However, despite its efficacy, this drug has significant side effects. The mechanism by which these undesired effects occur are not fully known. Research indicates the involvement of inhibition of some enzymes in this process. But nowadays other targets have been identified as corroboradores of the clinical complications by use ketoprofen, such as the oxidative stress. Oxidative stress is a deleterious condition for the organism that may be softened by the action of antioxidants such as catechins, tannins and other polyphenols. The relationship between oxidative stress, ketoprofen and the contribution of antioxidant molecules in this process need to be clarified and may be a future therapeutic target when it comes to improving the pharmacologic action and/or decreased side effects caused by use of ketoprofen. Thus, the aim of this study was to evaluate the action of ketoprofen and the aqueous extract of guarana alone and associates in oxidation in vitro and in vivo models of renal and hepatic toxicity studies evaluating biochemical and hematological laboratory parameters systems. Among the models used are direct action on ABTS•+, DPPH•, HOCl, O2•-, inhibition of peroxidase and hemolysis by AAPH radical. For the in vivo study, were used rats (female) (Wistar), which were divided into groups (n=10 or 11 animals): control group (saline), ketoprofen group (20 mg/kg/ day), aqueous extract guarana group 0,1 (0,1 mg/g/day), aqueous extract guarana group 1 (1 mg/g/day), association group 0,1 (ketoprofen (20mg/kg/day + water extract of guarana 0.1 mg/ g/day) and association group 1 (ketoprofen (20mg/kg/day + water extract of guarana 1 mg/g/ day), the administration of the samples was given by oral route (gavage) for 7 days. The results show that the aqueous extract of guarana show significant antioxidant activity in all in vitro tests. The ketoprofen virtually showed no activity in in vitro assays used in this study. The combination of these substances been shown to be potentially beneficial for action against free radicals and oxidizing agents, as well as in the inhibition of peroxidase . In in vivo assays, the ketoprofen caused significant changes in renal parameters: urea, creatinine and uric acid, and the association with the aqueous extract of guarana reversed this change. In hematological parameters, the ketoprofen caused anemia was not reversed by treatment with the extract. On markers of oxidative stress and antioxidant defense we observed variability in results, according to the indicator analyzed. In general, ketoprofen causes a decrease in the total antioxidant capacity and catalase levels of treated animals, and the aqueous extract of guarana contributed to re-establishment of this defense. On markers of oxidative stress and antioxidant defense we observed variability in results, according to the indicator analyzed. In general, the ketoprofen causes a decrease in the total antioxidant capacity and of the catalase levels of treated animals, and the aqueous extract of guarana contributed to re-establishment of this defense. The results are promising and indicate that the association between ketoprofen and the aqueous extract of guarana can be an alternative to reduce the potential damage linked to the use of this drug and considering the perspective addressed in this study. It is important to emphasize the importance of conducting studies to assess the maintenance of ketoprofen anti-inflammatory efficacy when used in combination with other substances.
Keywords: cetoprofeno; extrato aquoso de guaraná; estresse oxidativo; nefrotoxicidade; ketoprofen; aqueous extract of guarana; oxidative stress; nephrotoxicity; CNPQ::CIENCIAS DA SAUDE